2015
DOI: 10.1016/j.addbeh.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning in patients with alcohol-related liver disease post liver transplantation

Abstract: Psychosocial adjustment also improved significantly post liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 39 Following the transplantation surgery, significant improvements are generally seen in anxiety and depression symptoms. 40 However, patients may face mental distress and stress 41 associated with poor adherence. Life-long immunosuppressant therapy, medical monitoring, and the ever-present risk of graft rejection or failure are stress factors.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Following the transplantation surgery, significant improvements are generally seen in anxiety and depression symptoms. 40 However, patients may face mental distress and stress 41 associated with poor adherence. Life-long immunosuppressant therapy, medical monitoring, and the ever-present risk of graft rejection or failure are stress factors.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] However, a small number of patients posttransplant report the following disorders: major depression or recurrence of depression, [27][28][29][30][31][32] family dysfunction, 20,23,33 anxiety disorders, 34,35 and drug and/or alcohol abuse. [36][37][38][39][40] Therefore, the underlying conditions should be treated and will require close monitoring for emerging psychological symptoms before and after transplantation.…”
Section: Psychological Aspects In Transplantation Medicinementioning
confidence: 99%
“…Reviewing the patients' use of alcohol and exposure to illicit substances are an essential part of the evaluation process. [36][37][38][39][40] Careful review of consumption patterns, evidence of binge drinking, tolerance, adverse consequences of use, loss of control, and previous chemical dependence treatment is required. For patients with evidence of an abusive pattern of alcohol or substance use, chemical dependence treatment with ongoing participation in a sobriety program such as Alcoholics Anonymous provides the most comprehensive approach to support posttransplant sobriety.…”
Section: Substance Abusementioning
confidence: 99%
“…Several studies have been performed regarding the psychosocial factors of liver donors [25][26][27][28], but the psychosocial functioning of LT recipients with ALD has drawn little attention. Pegum et al found a decreased severity of depression and anxiety and improved quality of life among ALD patients after they received LT [26]. In a survey study, LT recipients with ALD demonstrated an obvious burden of substance use, mental health symptoms, and disability [29].…”
Section: Introductionmentioning
confidence: 99%